Audit firm, retain or rotation? (client and audit firm perspectives) - Gholamhossein Mahdavi; Abbas Ali Daryaei (Cogent Economics & Finance, 2017)
The purpose of this study is providing a framework for understanding the role of audit firm rotation in client expected value. And to explain the principles of client choice by auditor via specified models. We formalize this idea through stakeholder theory. Results show that the owners' expected outcome is increase in the level of reporting quality, all else held equal. Also client selection is a decrease in function with regard to the factors affecting it. Like the number of sub-branches, probability of good selection, probability of good perceived in a branch point, stages ahead and taking account of investigative intuition. We propose that retain-rotation audit firm vs. good or bad selection client relationship developed based on bid and ask process. Drawing on our analytical framework, we provide directions for further opportunities for research of client and audit firm.
Keywords: C6; G2; 330; audit firm; client selection; model